Effect of Membrane Solubilization on the Inhibition of Rat and Hamster Liver Microsomal Type I 11β-Hydroxysteroid Dehydrogenase by Bile Acids - Maeda, Y.; Funagayama, M.; Shinohara, A.; Koshimoto, C.; Komaki, K.; Furusawa, H.; Nakahara, H.; Yasuda, Y.; Machida, E. (Hormone and Metabolic Research, 2013)
The aim of this study was to investigate the differences between rats and hamsters, Two of the most widely used experimental animals, with respect to the effects of microsomal membrane solubilization on the inhibition of liver 11β-hydroxysteroid dehydrogenase (11β-HSDI) enzyme by bile acids. Liver microsome fractions were prepared, and the 11β-HSDI enzymatic activity was measured using cortisone as a substrate. The substrate and various concentrations of bile acids were added to the assay mixtures. After incubation, the products were extracted and analyzed using high-performance liquid chromatography. To investigate the effect of detergent on the inhibitory effects of bile acids, we conducted inhibition tests using Triton X-100-solubilized animal liver microsomes. When solubilized microsomes were used, all bile acids inhibited 11β-HSDI from rats and hamsters to various degrees. 7α-Hydroxycholanoic acids (cholic acid and chenodeoxycholic acid) in particular had strong inhibitory activities. In hamsters, 7β-hydroxycholanoic acid (ursodeoxycholic acid) was the strongest inhibitor among the bile acids tested, although its effect was not very strong. When nonsolubilized microsomes were used, deoxycholic acid did not inhibit but rather enhanced the enzymatic activity in both animals. Microsomal content of cholesterol and phospholipids are significantly different between rats and hamsters. Species differences in bile acid inhibition of nonsolubilized microsomes might be reflected not only by structural difference of bile acids, which affect membrane solubilization and enzyme activity directly, but also species difference in microsomal membrane lipid content.
Keywords: microsomes; solubilization; 11β-hydroxysteroid dehydrogenase; bile acid; rat; hamster